The U.S. newspaper industry’s relationship with online media 1980-2005 - Herndon, Keith Lamar (Curtin University, 2010)
This thesis examines from a historical perspective the issues and forces that shaped the U.S. newspaper industry during the formative years of the online era, specifically 1980 through 2005. The thesis explains this period as one of extreme change and transition as it explores the years leading up to the mid-1990s when newspaper publishers first confronted the Internet and adopted it as an online distribution platform. The thesis also discusses the early 2000s as the time when an Internet based media economy emerged to the detriment of newspaper business models. The thesis relies on the tenets of media industries scholarship, and in doing so, provides a thorough examination into the business relationships that existed between newspaper companies and online media forms during this period. Using numerous examples, the thesis details how newspaper companies viewed online media forms, how they deployed them, and for what purpose. The analysis of this activity provides insight about how the decisions made during this period influenced the newspaper industry’s economic condition at the end of the decade.The thesis explains from the perspective of the newspaper industry that the Internet arrived as part of a progression of technologies that had influenced the media during this period. Beginning with videotext through to proprietary online systems, the thesis demonstrates that these earlier platforms had informed newspaper companies how online media operates as a communication platform. The thesis discusses the importance of interactivity as a practical attribute of online media, but recounts how cultural and organizational artefacts kept newspaper companies from embracing interactive functions as they developed online products. As interactivity increasingly led to user empowerment during the Internet era, the thesis reveals how the reluctance of newspaper companies to cede or share content control with their audience placed them at a competitive disadvantage and contributed to discrediting the newspaper industry’s overall business model.